Post-attachment resistance to Striga hermonthica in finger millet (Eleusine coracana) - Kunguni, Josephine S.; Kibet, Willy; Oduori, Chrispus O.; Dida, Mathews M.; Anami, Sylvester; Kilian, Benjamin; Mutuku, Josiah M.; Runo, Steve; Odeny, Damaris A. (Wiley, 2025)
Finger millet is a highly nutritious and climate‐resilient cereal crop. Despite its importance, finger millet productivity in East Africa trails other cereals due to several biotic and abiotic factors, including the parasitic weed, Striga hermonthica. Striga spp. are noxious parasitic weeds whose damage can result in 100% yield losses in sub‐Saharan Africa. The objective of our study was to determine differences in post‐attachment responses of a selection of genotypes. We germinated finger millet in Petri dishes, transferred them to rhizotrons and infected the roots with Striga that had been pre‐conditioned for 7 days at 30°C and subsequently pre‐germinated using GR24. Histological analysis was done on three distinct genotypes to determine the host–pathogen interactions. The attachment of Striga onto the host was observed 3 days after inoculation. LESK10, a wild genotype, and OKHALE1 (cultivated) consistently supported fewer Striga plants after inoculation, while GBK029646A, a cultivated finger millet, consistently supported the highest. Histological analysis recorded an incompatible reaction in both OKHALE1 and LESK10 and a compatible reaction in GBK029646A as early as 3 days after infection. Our results suggest the likely existence of novel resistance in crop wild relatives that will be valuable for developing durable resistance to Striga in elite finger millet varieties.